(untitled) (GIST – Education and Learning Research Journal, 2007)
Teaching English to employees, and maintaining the language levels of those already hired, is a constant and growing concern for those responsible for corporate education in Colombia’s private sector. Although it might be argued that acquisition and maintenance of a second language is an individual responsibility, when faced with an increasingly globalized economy and the resultant use of English as the language of business, private enterprise in Colombia has had to intervene in a systemic problem resulting from deficiencies in private and public secondary and higher education, as well as in private language institutes.